11 Evaluation of tube potential effects on atherosclerotic plaque assessment: in vivo assessment with intravascular ultrasound. (15th May 2019) - Ramasamy, Anantharaman; Pugliese, Francesca; Moon, James C; Maurovich-Horvat, Pal; Mathur, Anthony; Baumbach, Andreas; Bourantas, Christos V
Abstract : Introduction: Computed tomographic coronary angiography (CTCA) is a non-invasive imaging modality which allows plaque burden (PB) and composition assessment. Lowering the tube potential (kilovolt [kV]) is key strategy to reduce radiation dose to patients. In vivo studies have not investigated the effects of lower tube potential (<120 kV) for plaque assessment. We aim to evaluate the effects of different kVs on plaque burden assessment in comparison to intravascular imaging. Methods: 11 patients with stable angina were prospectively recruited for a third generation dual-source CTCA (prospective ECG-triggered sequential scans, gantry rotation 250 ms, 128 × 2 × 0.5 mm collimation with tube voltage (kV) and current determined by scanner) and 3-vessel intravascular imaging (IVUS). The IVUS pullbacks were manually segmented and plaques with PB >40% were included in the study. Semi-automated CTCA segmentation of lumen and vessel wall borders were performed and corresponding plaques with IVUS were identified. The PB at the minimum lumen area in CTCA and IVUS were estimated and compared. Results: The mean age of the studied population was 61±11, 3 (27.2%) were diabetic and 7 (63.6%) suffered from hypercholesterolaemia. Group 1 (<100 kV) included 6 patients (16 plaques) while group 2 (≥100 kV) included 5 patients (11 plaques). CTCA-derived PB was similar between both groups – Group 1: 64.30±12.15% vs Group 2: 61.20±12.90%, p=0.551. However, Group 2 showed better correlation between IVUS and CTCA-derived PB (68.00±13.58% vs 61.20±12.90%, r=0.863, p=0.006) compared to Group 1 (59.79±9.66% vs 64.30±12.90%, r=0.222, p=0.427), respectively. Conclusion: Higher tube voltage threshold (≥100 kV) allows more accurate PB assessment in CTCA.